PERANCANGAN PURWARUPA SISTEM KEAMANAN KUNCI PINTU BERBASIS PENGENALAN WAJAH - Roihan, Ahmad; Supriyanti, Dedeh; Aziz, M Ardhana Herwandi; Hunaepi, Ahmad (Journal of Innovation And Future Technology (IFTECH), 2024)
Criminal acts often occur in recent times. In addition, each company also needs to create an instrument in the attendance administration process. Computer vision method by using human faces is used in this research. The method in this research is divided into three parts, namely data collection, analytical, and prototypes methods. To get maximum system design results, at least an analysis is needed to determine the system requirements. At the system design stage, the system is designed with images such as flowcharts and block diagrams. Testing using black box gets several evaluation results. The door lock system uses the facial recognition method, by matching the face image with the database that has been saved from the camera module captures. All data displayed in a web based application. This research is expected to assist companies in creating an automated attendance system, so that it can be useful as assisting companies in maintaining employee discipline and office security.